Growth behavior of CVD diamond films with enhanced electron field emission properties over a wide range of experimental parameters. Issue 12 (December 2018) - Jia, Xinyi; Huang, Nan; Guo, Yuning; Liu, Lusheng; Li, Peng; Zhai, Zhaofeng; Yang, Bing; Yuan, Ziyao; Shi, Dan; Jiang, Xin
Abstract: In this study, diamond films were synthesized on silicon substrates by microwave plasma enhanced chemical vapor deposition (CVD) over a wide range of experimental parameters. The effects of the microwave power, CH4 /H2 ratio and gas pressure on the morphology, growth rate, composition, and quality of diamond films were investigated by means of scanning electron microscope (SEM), X-ray diffraction (XRD), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). A rise of microwave power can lead to an increasing pyrolysis of hydrogen and methane, so that the microcrystalline diamond film could be synthesized at low CH4 /H2 levels. Gas pressure has similar effect in changing the morphology of diamond films, and high gas pressure also results in dramatically increased grain size. However, diamond film is deteriorated at high CH4 /H2 ratio due to the abundant graphite content including in the films. Under an extreme condition of high microwave power of 10 kW and high CH4 concentration, a hybrid film composed of diamond/graphite was successfully formed in the absence of N2 or Ar, which is different from other reports. This composite structure has an excellent measured sheet resistance of 10–100 Ω/Sqr. which allows it to be utilized as field electron emitter. The diamond/graphite hybrid nanostructure displays excellent electron field emission (EFE) properties with a low turn-on field of 2.17 V/μm and β = 3160, therefore it could be a promising alternative in field emission applications.